2020
DOI: 10.1111/ejn.14781
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting migratory journeys and changes in hippocampal astrocyte morphology in shorebirds

Abstract: Semipalmated sandpiper (Calidris pusilla) migration to the Southern Hemisphere includes a 5-day non-stop flight over the Atlantic Ocean, whereas semipalmated plover (Charadrius semipalmatus) migration, to the same area, is largely over land, with stopovers for feeding and rest. We compared the number and 3D morphology of hippocampal astrocytes of Ch. semipalmatus before and after autumnal migration with those of C. pusilla to test the hypothesis that the contrasting migratory flights of these species could dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 95 publications
(122 reference statements)
2
28
0
Order By: Relevance
“…The comparison of types I and II of C. semipalmatus with the corresponding morphotypes of C. collaris revealed higher mean values of morphological complexity and volume of the convex hull in the migrant and lower and higher mean values in the resident. We suggest that the differences found between migratory and nonmigratory birds' hippocampal astrocyte morphologies might be related to the adaptive response imposed by the contrasting long-distance migratory ights on learning and memory for recognition of olfactory, geomagnetic and visual cues during migration [17,22,23,86]. Indeed, in the present report when comparing migratory species with each other and with the non-migratory species, we found differences in all comparisons that may re ect adaptive responses to migration.…”
Section: The Morphological Complexity Of Astrocytes Is Greater In Migmentioning
confidence: 50%
See 4 more Smart Citations
“…The comparison of types I and II of C. semipalmatus with the corresponding morphotypes of C. collaris revealed higher mean values of morphological complexity and volume of the convex hull in the migrant and lower and higher mean values in the resident. We suggest that the differences found between migratory and nonmigratory birds' hippocampal astrocyte morphologies might be related to the adaptive response imposed by the contrasting long-distance migratory ights on learning and memory for recognition of olfactory, geomagnetic and visual cues during migration [17,22,23,86]. Indeed, in the present report when comparing migratory species with each other and with the non-migratory species, we found differences in all comparisons that may re ect adaptive responses to migration.…”
Section: The Morphological Complexity Of Astrocytes Is Greater In Migmentioning
confidence: 50%
“…In previous studies we investigated the in uence of the contrasting autumn migratory ights of C. pusilla and C. semipalmatus on hippocampal astrocyte morphology of birds captured in the Bay of Fundy (Canada) and in the coastal region of Bragança (Brazil). In this comparative analysis we found that long-distance migratory ight shapes the plasticity of hippocampal Type I and Type II astrocyte morphotypes in different ways, and suggested distinct physiological roles for these cells [22,23].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations